PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU - Ardandhi M. Hagi; Sasmita Jumiati; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of work discipline,motivation and morale on employee performance. This research was conductedon Jl. Papaya No. 57-59, Jadirejo, Kec. Sukajadi, Pekanbaru City, Riau 28121.The population in the study were 176 employees of the Riau Manpower andTransmigration Office, so using the slovin formula, the sample in this study was122 people. Data analysis in this study used multiple linear regression. Theresults of the study explain that partially and simultaneously work discipline,motivation and morale affect employee performance. While the adjusted R Squarevalue of 0.626 explains that the variables of work discipline, work motivation andwork enthusiasm can affect the performance variables of the Riau ProvinceManpower and Transmigration Office employees by 62.6% while the remaining37.4% are influenced by other variables not examined in this study . Keywords: Work Discipline, Motivation, Ape Spirit and Performance